Optimizing climate change communication: Context Comparison Model method - Seyranian, Viviane; Lombardi, Doug; Sinatra, Gale M.; Crano, William D. (Frontiers in Psychology, 2022)
The Context Comparison Model (CCM) provides a promising avenue to guide persuasive communication development by highlighting the features of the communication context that require consideration, including source, target, and task variables. The model was tested in a study of attitudes toward climate change. American participants read a text outlining scientific evidence for global climate change and a policy proposal to mitigate future climate change. Prior to reading the text, participants’ completed measures of their political affiliation (Republican, Democrats, Independent or Other) to render their group memberships salient. They were randomly assigned to one of four text x source conditions. The text was attributed as originating from an: (a) ingroup minority; (b) ingroup majority; (c) outgroup minority; or (d) outgroup minority. Participants completed pre- and post-measures of attitudes and their perception of the subjective or objective status of the attitude. Pretest scores revealed that global climate change attitudes were held less strongly by Republicans than Democrats. In line with expectations, participants’ subjective attitudes were more influenced by ingroup sources, and larger persuasive effects were obtained for ingroup minorities. For objective judgments, participants were more persuaded by an outgroup source, and larger effects were evident for outgroup majorities. Results were precisely predicted by the CCM. Their implications for science communication were discussed.